PENGARUH DIMENSI KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI BALAI KARANTINA IKAN, PENGENDALIAN MUTU DAN KEAMANAN HASIL PERIKANAN MEDAN I - Amiruddin Ritonga; Humaini Nasution; Aswiluddin .; Sry Liswati (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this study are: How much influence the knowledge, skills and abilities have on employee performance. This study aims to determine the effect of knowledge, skills and abilities on employee performance. Taking the sample using total sampling technique, the sample of this study amounted to 37 people. Knowledge partially has a positive effect on employee performance; Skills partially have a positive effect on employee performance; Ability partially has a positive effect on employee performance; Knowledge, skills and abilities have a positive and significant impact on employee performance Fish Quarantine Center, Quality Control and Safety of Fishery Products I.